2010
DOI: 10.1111/j.1600-6143.2009.02943.x
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Clusters Differentiate Subgroups Within the Nonspecific Diagnoses of CAN or CR: Preliminary Data from the DeKAF Study

Abstract: The nonspecific diagnoses 'chronic rejection' 'CAN' , or 'IF/TA' suggest neither identifiable pathophysiologic mechanisms nor possible treatments. As a first step to developing a more useful taxonomy for causes of newonset late kidney allograft dysfunction, we used cluster analysis of individual Banff score components to define subgroups. In this multicenter study, eligibility included being transplanted prior to October 1, 2005, having a 'baseline' serum creatinine ≤2.0 mg/dL before January 1, 2006, and subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 20 publications
4
79
1
1
Order By: Relevance
“…This finding agrees with recently published studies (25)(26)(27)(28)(29). Wavamunno et al (30) showed that endothelial and subendothelial ultrastructural abnormalities in glomerular and peritubular capillaries are sensitive early markers of CTG.…”
Section: Discussionsupporting
confidence: 82%
“…This finding agrees with recently published studies (25)(26)(27)(28)(29). Wavamunno et al (30) showed that endothelial and subendothelial ultrastructural abnormalities in glomerular and peritubular capillaries are sensitive early markers of CTG.…”
Section: Discussionsupporting
confidence: 82%
“…The DeKAF study of deteriorating kidneys biopsied for cause, has most recently reconfirmed the role of inflammation in biopsies from patients with chronic kidney dysfunction, no matter where it is found in the kidney, as a major predictor of graft loss in the first 3 years after transplantation (19). However a different publication from this study has identified CNI nephrotoxicity as the local pathological diagnosis in 30% of failing grafts and substantial arteriolar hyalinosis as a feature of two of the major groupings (20). The Mayo clinic series of 1-and 5-year protocol biopsies has also recently questioned the frequency, progressive nature and specificity of chronic CNI toxicity (21).…”
Section: Chronic Cni Nephrotoxicitymentioning
confidence: 71%
“…Moreover, allografts labeled as calcineurin inhibitor toxicity fared no worse than other grafts in the absence of this diagnosis (11). The preponderance of abnormalities in this study featured immunologic injury including acute rejection (12) and antibody-mediated injury (13). Moreover, the presence of inflammation in the allograft, in areas of fibrosis and TA, was an independent negative feature of allograft failure (14).…”
Section: Clinical Differentialmentioning
confidence: 84%